PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3), LINGKUNGAN KERJA, DAN PELATIHAN TERHADAP KINERJA PADA PT PELABUHAN INDONESIA II (PERSERO) JAKARTA (Studi Kasus Pada Proyek Pengerukan Pembangunan TPK Kalibaru) - Roharto, Titing; Kasmir, K (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
The research was conducted with the aim to know and analyze the influence of Occupational Safety and Health (OSH), Work Environment and Training on Performance at PT Pelabuhan Indonesia II (Persero) Jakarta.  The method used in this research is quantitative research with causality research approach. The population in this study are all employees who work at PT Pelabuhan Indonesia II (Persero), especially employees who duty on the direct operational activities at New Priok Container Terminal Dredging Project with a population of 320 employees. Sampling technique based on Slovin formula at 95% confidence level so that obtained as many as 178 sample people.  Based on the test results obtained that the safety and health effects significantly affect the performance of the company PT Pelabuhan Indonesia II (Persero) on New Priok Container Terminal (NPCT) Dredging Project. Work environment significantly affects the performance of the company PT Pelabuhan Indonesia II (Persero) on New Priok Container Terminal (NPCT) Dredging Project. Training has a significant effect on the performance of PT Pelabuhan Indonesia II (Persero) at New Priok Container Terminal (NPCT) Dredging Project